Host Community Attitudes Towards Internally Displaced Persons: Evidence from Al-Bab, Syria - Abedtalas, Musallam; Mamo , Adnan Rashid (Journal of Social and Development Sciences, 2023)
Considering the unique context of the Al-Bab area in Syria hosting Internally Displaced Persons (IDPs), we tested the role of economic individual self-interest in shaping a host community’s attitude towards IDPs. The findings from analyzing data collected from 496 households indicated that self-interest had a significant effect on their attitudes. Interestingly, when positive and negative attitudes were isolated from each other, the findings revealed that the factors shaping the former may not always be the same for the latter. The particular value of this study is in exploring the host community’s attitude towards IDPs, something which has not been studied and thus contributes to enhancing our knowledge about the attitude towards newcomers.